Lyapunov redesign for a class of uncertain systems with delays. (December 2021) - Gomez, Marco A.; Cruz-Ancona, Christopher D.; Fridman, Leonid
Abstract: We address the robust stabilization problem of a general class of uncertain linear systems with multiple delays from a Lyapunov redesign (LR) methodology that relies on Sliding Mode Control (SMC) theory. The proposed approach, which is based on a well-known (yet not used for LR) class of Lyapunov–Krasovskii functionals, allows us to enlarge the type of uncertain systems with delays that can be stabilized. The uncertainties of the system are compensated within a delay-free sliding manifold that is taken from the time-derivative of the considered functional.